Hak Aborsi Wanita Tanpa Persetujuan Suami Dalam Perspektif Hukum Keluarga Islam - Wahyudi; Oyo Sunaryo Mukhlas; Beni Ahmad Saebani (Sekolah Tinggi Agama Islam Taruna Surabaya, 2026)
This study discusses women's right to abortion without the husband's consent from the perspective of Islamic family law. The main focus of this study is to explore how Islam views women's reproductive rights in the context of abortion decision-making, especially when the decision is made without involving the husband. This study uses a normative approach by referring to primary sources such as the Qur'an, Hadith, and jurisprudence books, as well as secondary sources in the form of scholars' fatwas and contemporary literature. The analysis results indicate that Islam allows women to make decisions regarding their health, including abortion in cases of medical emergencies or pregnancy due to rape. However, the principle of joint responsibility in marriage also requires the involvement of the husband in such decision-making. Conflicts between women's reproductive rights and the rights of husbands often arise due to differences in views on the priorities of justice and maslahah (well-being). Abortion without the husband's consent can have a negative impact on household harmony, such as communication breakdowns, distrust, and moral conflicts. Therefore, the proposed solution is the application of the principle of consultation (musyawarah) as an effort to reach a fair and beneficial agreement for all parties.